Teachers' Efforts in Addressing Students' Misconceptions on Force and Its Effects in Elementary Science and Social Studies - Ari Astuti; Yun Ratna Lagandesa; Sisriawan Lapasere; Zulnuraini Zulnuraini; Ryan Andhika Pratama (Papanda Publisher, 2026)
Misconceptions in elementary science learning—particularly in the concept of force and motion—remain a persistent obstacle to achieving meaningful conceptual understanding. Despite growing research on misconception identification, little is known about how teachers actively address these misconceptions within the Science and Social Studies (Ilmu Pengetahuan Alam dan Sosial/IPAS) framework under the Merdeka Curriculum. This study employed a qualitative descriptive design involving one fourth-grade teacher and 23 students at SD Inpres 3 Talise, Palu City. Data were collected through structured classroom observations across five lessons, a semi-structured teacher interview, a validated ten-item Likert-scale student questionnaire (α = .87), and documentation review, and were analyzed using the Miles et al. (2014) framework. Three dominant misconceptions were identified: force as push-only, object mass as the sole determinant of mobility, and force as requiring visible contact. The teacher employed five integrated strategies—diagnostic questioning, concrete demonstrations, collaborative discussion, immediate corrective feedback, and concept reinforcement—supplemented by adaptive video use for abstract concepts. Student perceptions were strongly positive (83.37%). These findings align with conceptual change theory and underscore the centrality of adaptive pedagogical content knowledge in effective misconception remediation. This study contributes empirical documentation of responsive teacher practice within an underrepresented curriculum context and provides practical guidance for elementary science teacher development.